Pengembangan Bahan Ajar Interaktif berbentuk Flipbook Berbasis VCT pada Pembelajaran Pendidikan Pancasila di Kelas IV Sekolah Dasar - Fitriani, Siska; Rahmatina, Rahmatina (Asian Journal of Early Childhood and Elementary Education, 2025)
The limited use of interactive instructional materials based on information technology by teachers has contributed to low student motivation in learning. This study aims to develop interactive instructional materials in the form of a flipbook based on the Value Clarification Technique (VCT) for teaching Pendidikan Pancasila in fourth-grade elementary school. The research employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through validation questionnaires completed by content, language, and media experts, as well as practicality questionnaires filled out by teachers and students. The trial subjects included 18 fourth-grade students from UPT SDN 23 Batipuah Baruah, while the main research subjects were 12 students from UPT SDN 24 Gunuang Rajo. The results showed a validity score of 94.16% (categorized as highly valid), with expert assessments as follows: content expert 87.5%, language expert 97.5%, and media expert 97.5%. The practicality test yielded 96.25% from the teacher and 93.35% from the students (both categorized as highly practical), while the effectiveness test scored 94.33% (highly effective). These findings confirm that the VCT-based interactive flipbook is valid, practical, and effective for use in Pendidikan Pancasila instruction in fourth-grade elementary classrooms.